Combined approach using uniportal video-assisted thoracoscopic surgery in left tracheal sleeve pneumonectomy - Aim, Allan; Almre, Ingemar; Vanakesa, Tõnu (Journal of Thoracic Disease, 2018)
Left tracheal sleeve pneumonectomy is rare and challenging surgical procedure with high postoperative complication and mortality rates. We describe the least invasive single-stage surgical approach using uniportal video-assisted thoracoscopic surgery (VATS) currently successfully applied for a left centrally located bronchogenic carcinoma with tracheal involvement. This case shows how uniportal VATS can be effectively used in challenging cases for reducing invasiveness without compromising patient safety nor oncological principles of complete surgical resection.